Increased Intracranial Pressure in Acute Disseminated Encephalomyelitis. (February 2019) - Orbach, Rotem; Schneebaum Sender, Nira; Lubetzky, Ronit; Fattal-Valevski, Aviva
Objective: To assess the intracranial pressure in pediatric acute disseminated encephalomyelitis using spinal tap opening pressure on lumbar puncture, which is routinely performed as part of suspected acute disseminated encephalomyelitis workup. Compared to other cerebrospinal fluid parameters such as cell count, protein concentration, and presence of oligoclonal bands, cerebrospinal fluid opening pressure is infrequently recorded. Methods: A retrospective chart review of demographic, clinical, and laboratory data of children diagnosed with acute disseminated encephalomyelitis admitted to a tertiary referral hospital between 2005 and 2016. Results: Of the 36 children diagnosed with acute disseminated encephalomyelitis, 24 had the cerebrospinal fluid opening pressure documented in their records. The mean cerebrospinal fluid opening pressure was 27.6±12.6 cmH2 O, range 9-55 cmH2 O (95% confidence interval 21.9-33.6). Cerebrospinal fluid opening pressure in the acute disseminated encephalomyelitis group was statistically significantly higher ( P = .0013, 95% confidence interval 4.2-15.0) than the accepted upper limit in this age group (18 cmH2 O). In 10 of 24 patients (42%), the opening pressure was above 28 cmH2 O. Conclusions: Increased opening pressure was the most frequent cerebrospinal fluid abnormal finding in our cohort, which suggests a potential role of increased intracranial pressure in the acute disseminated encephalomyelitis pathophysiological disease mechanism. In certain cases, the opening pressure value could have monitoring and therapeutic implications, and therefore its measurement is highlighted by this study.